2019
DOI: 10.7475/kjan.2019.31.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Functional Health of Patients with Chronic Insomnia based on Theory of Unpleasant Symptoms

Abstract: The purpose of this study was to identify factors influencing functional health of patients with chronic insomnia based on the Theory of Unpleasant Symptoms (TOUS). Methods: Data were collected from 184 patients with chronic insomnia who had been treated at the sleep center in hospital in South Korea. Data were collected from 23 December 2014 to 18 May 2015 through self-reported questionnaires from pre-sleep arousal, worry, perceived stress, social support, insomnia symptom, and functional health. Data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our theoretical framework focuses on integrating the concepts of nomophobia, anxiety, depression, stress, insomnia as well as impulsivity based on different studies associating theses variables together (Fig 1) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Our theoretical framework focuses on integrating the concepts of nomophobia, anxiety, depression, stress, insomnia as well as impulsivity based on different studies associating theses variables together (Fig 1) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A prior study applying TOUS for colon cancer patients reported symptoms from illness and surgery negatively correlated with a physical component score and a mental component score for quality of life [41]. Another using TOUS for chronic insomnia found that perceived stress, presleep arousal, and social support influenced in-somnia; while insomnia affected functional health [42]. In this study, menopausal symptoms mediated HRQoL in women during MT and early postmenopausal stage during which women may experience menopausal symptoms.…”
Section: Discussionmentioning
confidence: 54%